Influence of pH on Fumaric Acid Adsorption by Basic Ion-Exchange Resins - Fu, Yong-Qian; Zhu, Hua-Yue; Jiang, Ru; Yin, Long-Fei; Ruan, Qi-Cheng; Ren, Shi-Bin (Asian Journal of Chemistry, 2013)
The effects of pH on the adsorption of fumaric acid by basic ion-exchange resins were investigated. The adsorption isotherms of the strong-base resin IRA-400 and the weak-base resin IRA-94 were investigated with aqueous solutions of fumaric acid at different pH and the equilibrium adsorption data obtained being very well fitted by the Freundlich model. The pseudo-first-order and pseudo-second-order kinetic models were applied to describe the kinetic data, with the pseudo-second-order model providing a perfect fit. The value of equilibrium rate constant k2 indicated that the equilibrium rate of IRA-400 resin was much faster than that of IRA-94 resin, but there was no evident discrepancy at different pH for each resin. Breakthrough curves of two resins at different pH were also investigated. The efficiency of adsorption column of IRA-400 resin had no evident correlation with the pH; while the efficiency of adsorption of IRA-94 resin decreased from 64-31 % as the pH increased from 2.0-5.0.